GREEN ENTREPRENEURSHIP: A SECURED MODE OF SUSTAINABILITY AND ITS PROSPECTS IN ASSAM - Sharma, Sweta; Sharma, Seema; Barman, Rajesh Deb; Choudhury, Sangeeta (International Journal of Psychosocial Rehabilitation, 2020)
Green economy is a means for reconciling environment and economic development. Green entrepreneurship facilitates the use of those methods of production which do not destabilise the environment. Green entrepreneurship and sustainable development are closely knit terms. Green entrepreneurship is the need of the hour for promoting sustainable growth in India. Green entrepreneurship is a collective responsibility on the part of the government, civil society, companies and all the other stakeholders of a country. It is irony that the concept is still at its nascent stage in India, especially in Assam. Until and unless people are aware of the concept of green entrepreneurship and sufficient training, support and infrastructure is available for the same, green entrepreneurship can never translate into reality. The study is an attempt to analyse the interwoven dynamics of green entrepreneurship and sustainable developmentand highlight the crucial areas offering prospects for green entrepreneurship in Assam.To study emphasises upon the role of government, civil society and companies (via CSR) in promoting green entrepreneurship. The study also tries to find out how aware the people of Assam are about green entrepreneurship and whether they would really like to undertake green projects in future. The study reveals that very few people are aware of the concept and most of them are interested in green entrepreneurship projects, provided they are given due training and required assistance.